Reference Values for Shear Wave Elastography of Neck and Shoulder Muscles in Healthy Individuals - Ewertsen, Caroline; Carlsen, Jonathan; Perveez, Mohammed Aftab; Schytz, Henrik (Ultrasound International Open, 2018)
Purpose to establish reference values for ultrasound shear-wave elastography for pericranial muscles in healthy individuals (m. trapezius, m. splenius capitis, m. semispinalis capitis, m. sternocleidomastoideus and m. masseter). Also to evaluate day-to-day variations in the shear-wave speeds and evaluate the effect of the pennation of the muscle fibers, ie scanning parallel or perpendicularly to the fibers.Materials and Methods 10 healthy individuals (5 males and 5 females) had their pericranial muscles examined with shear-wave elastography in two orthogonal planes on two different days for their dominant and non-dominant side. Mean shear wave speeds from 5 ROI’s in each muscle, for each scan plane for the dominant and non-dominant side for the two days were calculated. The effect of the different parameters – muscle pennation, gender, dominant vs non-dominant side and day was evaluated.Results The effect of scan plane in relation to muscle pennation was statistically significant (p<0.0001). The mean shear-wave speed when scanning parallel to the muscle fibers was significantly higher than the mean shear-wave speed when scanning perpendicularly to the fibers. The day-to-day variation was statistically significant (p=0.0258), but not clinically relevant. Shear-wave speeds differed significantly between muscles. Mean shear wave speeds (m/s) for the muscles in the parallel plane were: for masseter 2.45 (SD:+/−0.25), semispinal 3.36 (SD:+/−0.75), splenius 3.04 (SD:+/−0.65), sternocleidomastoid 2.75 (SD:+/−0.23), trapezius 3.20 (SD:+/−0.27) and trapezius lateral 3.87 (SD:+/−3.87).Conclusion The shear wave speed variation depended on the direction of scanning. Shear wave elastography may be a method to evaluate muscle stiffness in patients suffering from chronic neck pain.
Keywords: muscular; ultrasound; elastography